Innovation activity in European Union service sector: Similarities or differences? - Kamil Decyk (International Entrepreneurship Review)
Objective: The article aimed to identify and assess the degree of homogeneity and differentiation of European Union countries regarding innovation activity in individual sections of the service sector.